Determinants of Women Participation in Cassava Production in Imo State, Nigeria - Ejechi, Mercy E.; Okoye, B. C; Eluagu, C. J.; Aboajah, F. N.; Madu, T. U. (Journal of Science, Technology and Innovation Research, 2026)
The study analyzed how socioeconomic factors and newly released cassava varieties impact women’s participation and income generation in the value chain, aiming to promote gender-inclusive agricultural development. This study examines the demographic and socioeconomic characteristics of women involved in cassava production. Most participants are middle-aged (31–50 years), married, and head large households, highlighting their central role in household sustenance and income generation. The majority possess secondary education, which may enhance their adoption of improved practices. Women predominantly farm small plots (1–2 hectares), reflecting persistent land access constraints. Annual earnings are modest, with most earning ₦101,000–₦200,000, indicating limited economic empowerment. Farmers prioritize high-yielding cassava varieties, though early maturity and income potential are also valued. These findings underscore the need for interventions targeting land access, improved varieties, and market opportunities. Ordinary least squares regression analysis revealed that 82.17% of the variability in women’s participation in cassava production in Imo State is explained by key socio-economic factors. Age and household size showed significant negative effects, indicating that older women and those from larger households are less likely to participate. In contrast, marital status, education, farmers’ association membership, and access to credit all had positive and significant impacts, with education and association membership being especially influential. Regarding income control, only 22.22% of women had full autonomy over cassava sales revenue, while the majority (77.78%) shared decision-making, highlighting both collaborative and independent financial roles within households. Key words: Women, Cassava, participation, Income generation